Export Diversi cation in a Transitioning Economy : The Case of Syria - Lim, Jamus Jerome; Saborowski, Christian (2012)
How does the process of export diversification play out in a transitioning economy, especially in light of government policy aimed at trade liberalization? This paper examines this question by considering a directed policy effort by Syria -- an economy transitioning from both economic centralization and resource dependence -- to liberalize its trade in 2001. In addition to documenting the patterns of diversification at the aggregate level since the implementation of the policy, we also examine factors that are related to diversification at the sectoral level. Our findings suggest that, while Syria has achieved reasonably rapid export diversification, this may to a large extent be the result of structural transformations in the economy, and that further consolidation of diversification gains may require continued policy reform along the lines of strengthening Syria's weak institutional and business environment.